IMPACT DE LA GOUVERNANCE FONCIÈRE SUR LES INVESTISSEMENTS DIRECTS ÉTRANGERS EN AFRIQUE SUBSAHARIENNE - Marius Bendoma; Franky Brice Kogueda Afia; André Marie Ndzie Ndzobo (African Journal on Land Policy and Geospatial Sciences, 2025)
Contexte :